RSS and Gandhi - Ragi, Sangit Kumar, author.
1 online resource
Keywords: "This book explores the relationship between Gandhi and the Rashtriya Swayamsevak Sangh (RSS)--a right-wing Indian organisation and discusses their relevance in India's history and the socio-political discourse. It looks back at Indian independence movement and the key debates and issues that the country was confronted with in the early 1900s which continue to be relevant today. These include the practice of untouchability, tensions and conflicts between communities, the treatment of minorities and the marginalised, debates on the ideology of Hindutva, religious conversion, questions on cultural and civilizational identity of India and responses to the Western modernity. This book discusses the ideological differences between Gandhi and RSS while also focussing on areas where they converged. This book will be of interest to students, researchers, and academics working in the area of modern Indian history, political science and philosophy. It will also be an interesting read for general readers curious to know understand more about Gandhi and the RSS"--